Association between lower urinary tract symptoms and cardiovascular risk scores in ostensibly healthy women. (29th October 2018) - Lee, Hyun Young; Moon, Ji Eun; Sun, Hwa Yeon; Doo, Seung Whan; Yang, Won Jae; Song, Yun Seob; Lee, So‐Ryoung; Park, Byoung‐Won; Kim, Jae Heon
Abstract : Objectives: To investigate the association between lower urinary tract symptoms (LUTS) and cardiovascular disease (CVD) risk in women, as severe LUTS are known to be associated with CVD risk in men but few studies have focused on this issue in women. Subjects and Methods: A total of 1014 ostensibly healthy women, who participated in a voluntary health check in a health promotion centre from November 2013 to October 2015, were enrolled. LUTS were assessed using the International Prostate Symptom Score (IPSS) and Overactive Bladder Symptom Score (OABSS). CVD risk scores were calculated using the Framingham risk score and the American College of Cardiology/American Heart Association Atherosclerotic Cardiovascular Disease (ASCVD) score. Correlation, partial correlation, and multiple logistic regression analyses were conducted. Results: The mean age and body mass index (BMI) of the women were 51 years and 22.6 kg/m 2, respectively. The ASCVD score showed significant positive correlations with IPSS items Question 2 (Q2), Q3, Q5, and Q7 (all P < 0.05), total IPSS ( P = 0.001), IPSS storage ( P = 0.006) and IPSS voiding symptoms scores ( P = 0.001) based on partial correlation analysis after adjustment for BMI. For the OABSS, the ASCVD score showed significant positive correlations with OABSS items Q2, Q3, and Q4 ( P < 0.001, P = 0.017, and P < 0.001, respectively) and total OABSS ( P < 0.001). Multiple logistic regression analysis showed that the moderate–severe risk groups of the OABSS and IPSS were associated with the ASCVD risk score in adjusted models ( P < 0.001) compared to the none–mild OABSS and mild IPSS groups. After adjustment for age and BMI, IPSS storage score was significantly related with the ASCVD risk score ( B = 0.855, P = 0.016) Conclusions: LUTS, especially storage symptoms, might be risk factors for predicting future CVD risk in women. Further prospective or cohort studies are needed to validate this possibility.